Stabilizing RNA Nanovaccines with Transformable Hyaluronan Dynamic Hydrogel for Durable Cancer Immunotherapy. (11th November 2022) - Jia, Fuhao; Huang, Wenping; Yin, Yue; Jiang, Yue; Yang, Qingzhen; Huang, Haishui; Nie, Guangjun; Wang, Hai
Abstract: Massage RNA (mRNA) vaccines represent a new strategy for advanced cancer immunotherapy. To protect mRNA from degradation and deliver to targeted cells, lipid nanoparticles (LNPs) are extensively utilized as non‐viral vectors. However, the stability of mRNA‐laden LNPs substantially hinders their clinical application. Development of thermostable and durable mRNA nanovaccines is urgently needed. Here, a hyaluronan dynamic hydrogel is reported to protect mRNA and resiquimod (R848)‐laden LNPs (HA‐mRLNPs) from degradation at room temperature for durable cancer immunotherapy. A microfluidic device is proposed to effectively encapsulate mRNA and immunoadjuvants in LNPs (mRLNPs). Then, hyaluronan dynamic hydrogel is used to stabilize LNPs during storage at room temperature by restricting the migration and fusion of LNPs. Particularly, gel‐like hyaluronan undergoes state transition for controlled release of mRLNPs under physiological condition. Therefore, HA‐mRLNPs can efficiently deliver mRNA encoding tumor antigens to dendritic cells for antigen presentation to induce antigen‐specific CD8 + T cells for killing tumor cells. Overall, this study demonstrates that the LNPs‐hydrogel system can be used for effective cancer immunotherapy. Abstract : The fusion or aggregation of lipid nanoparticles is prevented by embedding in hyaluronan dynamic hydrogel. This hybrid RNA nanovaccines can be stored at room temperature for at least 2 weeks. At the same time, this system is also suitable for sustained release in vivo for durable cancer immunotherapy.